LEGAL EFFORTS TO INTEREST IN LAND FOR INDONESIAN CITIZENS THE NOMINEE AS ​​TAXPAYERS - I Ketut Dody Arta Kariawan; Simon Nahak; I Nyoman Alit Supadma (Jurnal Hukum Prasada, 2018)
Abstract Indonesian citizen is included as a taxpayer. In relation to the nominee agreement, the land of the guarantee object is included in the assets obtained from the government's tax amnesty program. In this paper, the purpose of the analysis is to know and examine how the legal consequences for Indonesia citizens who become nominee on the interest in land with the tax amnesty program and how the legal efforts that can be done by the citizen if the foreigners violate the nominee agreement related to the payment of tax on the rights soil. Type of research used in this paper is normative law research. The results of this study indicate that (1) the legal consequences for Indonesian citizens who become nominee to the right to land with the existence of tax amnesty program that is criminal law, civil law and criminal law of taxation. (2) legal protection to the holder of the land title certificate as a legal remedy which can be done by the citizen if the foreigner violates the nominee agreement related to the payment of tax on the right of land is able to take a non-litigation path through mediation. If the settlement cannot be conducted through mediation, it can be done through a court of law with the judicial discovery made by the judge in resolving the dispute. Keywords: Efforts, Indonesia Citizens, Nominee, Tax amnesty